Psychiatric Illness and Behavioural Problems in Adults with Learning Disability and Epilepsy - Shoumitro Deb; Joseph Joyce (Behavioural Neurology)
We retrospectively collected data on the rate and type of psychiatric illness and behavioural problems on 143 adults with learning disability and epilepsy. 55% behavioural problems. 19% verbal aggression and temper tantrums, and 13% injurious behaviour. The overall rates of behavioural problems and different types of behaviours found in the current study cohort are similar to what was found before in learning disabled adults in general, as well as in epileptic and non-epileptic learning disabled adults. Psychiatric diagnosis was made in 12.6% combined diagnosis of schizophrenia, delusional disorder and schizo-affective disorder was most common (5%) diagnosis of depressive episode (3%) bipolar affective disorder.